Who owes what to war refugees - Kling, Jennifer (Journal of global ethics, 2016)
The suffering of war refugees is often regarded as a wrong-less harm. Although war refugees have been made worse off in severe ways, they have not been wronged (in some cases), because no one intentionally caused their suffering. In military parlance, war refugees are collateral damage. As such, nothing is owed to them as a matter of justice, because their suffering is not the result of intentional wrongdoing; rather, it is the regrettable and unintended result of necessary and proportionate wartime actions. So, while the warring national or extra-national groups might help war refugees, such aid is regarded as humanitarian, not as justice.I challenge the view that war refugees are harmed but not wronged when those harms directly result from necessary and proportionate wartime actions. War refugees are innocent bystanders, and so are an exception to the principle that permits defense by any necessary and proportionate means. Just as an individual may not kill or seriously harm an innocent bystander to save herself, so too national or extra-national groups may not create refugees to win a war. If such groups do create war refugees during the legitimate pursuit of military goals, they have wronged those refugees, and so owe them recompense.